The Tour de France: an updated physiological review - Santalla, A.; Earnest, C. P.; Marroyo, J. A.; Lucia, A. (International Journal of Sports Physiology and Performance, 2012)
From its initial inception in 1903 as a race premised on a publicity stunt to sell newspapers, the Tour de France had grown and evolved over time to become one of the most difficult and heralded sporting events in the world. Though sporting science and the Tour paralleled each other, it was not until the midlate 1980s, and especially the midlate 1990s (with the use of heart-rate monitors) that the 2 began to unify and grow together. The purpose of this brief review is to summarize what is currently known of the physiological demands of the Tour de France, as well as of the main physiological profile of Tour de France competitors.